Effects and recovery of small-scale fluctuations in one-way nesting for regional ocean modeling. (January 2020) - Pham, Van Sy; Hwang, Jin Hwan
Abstract: With regional ocean models, generating small-scale structures is important in dynamical downscaling using the nesting method. Numerous studies have shown that the generation of small-scale features is driven by large-scale flows and information supplied at the lateral boundaries by a global-scale model or observations, along with local forcing. This work, however, finds that the conventional downscaling approach reproduces small-scale motions too weakly even to sustain the energy of the larger scales, leading to degradation of the nested simulation. Therefore, this work investigates the reason for the underestimation related to the stimulating sources evoking small-scale motions. Along with that, an efficient method is proposed to improve the quality of simulation results even though a stimulating source does not exist in the domain of simulation. In this method, the addition of artificial small-scale fluctuations along the boundaries greatly enhances the reproducibility of the model, even if there is a large spatial resolution jump between the driving data and the driven model. Highlights: Downscaling from the coarser information always loses small-scale information. Small-scale motions cannot fully develop without supporting stimulated sources. Such deficiencies in small scales distort the energy distribution at larger-scales. The artificial introduction of small-scale motions enhances the downscale ability.